Inflation Targeting Policy: What Role Can It Play In The Recovery Of Morocco’s Economic Situation? - SAAD-ALLAH, Imane (Revue Internationale du Chercheur, 2023)
In a turbulent global context marked by instability following the Covid-19 health crisis and the war in Ukraine, Morocco’s economic situation had to suffer several damages. Among these impacts is inflation. Faced with price instability, it seems crucial to question the conduct of current monetary policy. In this sense, this article seeks to highlight the importance of rethinking Morocco’s monetary policy in order to overcome the effects of the economic recession. Price stability being one of the main objectives of the BAM[1], could only be ensured by the presence of a monetary regime capable of intervening in periods of crisis for the absorption of shocks and likely to bring inflation back to its equilibrium as quickly as possible. As the inflation targeting policy is the most widespread regime in the world today, inflation targeting policy continues to pique the interest of economists. In this paper, it will be a question of highlighting the literature review which has discussed this new regime and of examining to what extent its adoption could allow the regulation of inflation in the case of Morocco as well as the conditions under which non-implementation could constrain its implementation. [1] Bank Al-Maghreb